Iowa Birdline update, October 15, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for October 15, 1990. Highlights of the update include the sightings of a Mew Gull and a Sharp-tailed Sandpiper as well as the continued presence of a California Gull and a Scissor-tailed Flycatcher. Also of note was a one day observation of 81 total species, including 14 shorebird species at Coralville Lake. Others interesting sightings were of 10,000 Tree Swallows and 12 species of sparrows, including a Le Conte's and a Lincoln's. Epson - sheet feed/flatbed